Cardiovascular-protective effects of blueberry consumption in postmenopausal women with above-normal blood pressure - Woolf, Emily K., author; Johnson, Sarah A., advisor; Gentile, Christopher L., committee member; Weir, Tiffany L., committee member; Rao, Sangeeta, committee member (Colorado State University. Libraries, 2023)
Endothelial dysfunction is the first step in atherosclerosis and contributes to its progression, and thus, is central to cardiovascular disease (CVD). It is driven by excessive oxidative stress and inflammation and characterized by impaired endothelium-dependent dilation. Estrogen-deficient postmenopausal women have oxidative stress-mediated suppression of endothelial function that is worsened by high blood pressure. Chronic blueberry consumption may be a beneficial dietary intervention for this population as it has shown to improve vascular function and blood pressure, though some studies have not demonstrated efficacy possibly due to the observed high interindividual variability in response to the intervention. Evidence indicates blueberries improve endothelial function, but studies have not been performed in postmenopausal women. Furthermore, ex vivo research has shown that blueberry (poly)phenols and their metabolites can decrease endothelial oxidative stress and inflammation, but whether these mechanisms translate to humans is unclear. The objectives of this dissertation were to 1) examine the efficacy of chronic blueberry consumption to improve endothelial function and blood pressure in estrogen-deficient postmenopausal women with above-normal blood pressure, with a specific focus on identifying mechanisms for improving endothelial function, 2) identify factors that contributed to the efficacy of blueberries as a dietary intervention for improving endothelial function, and 3) explore cellular mechanisms responsible for endothelial function improvements and the anti-atherogenic potential of blueberries. To investigate the aforementioned, we conducted a randomized, double-blind, placebo-controlled clinical trial and assessed endothelial function (measured through flow-mediated dilation (FMD)) and supine brachial blood pressure before and after daily consumption of 22 g of freeze-dried highbush blueberry powder or isocaloric placebo powder for 12 weeks. To examine mechanisms for improved endothelial function, FMD was assessed before and after infusing a supraphysiological dose of the antioxidant ascorbic acid (i.e. vitamin C) and normalized to shear rate area under the curve (FMD/SRAUC). To investigate factors impacting the interindividual variability in the endothelial function responses after the 12 weeks of blueberry consumption, we grouped the blueberry treatment group into responders (≥ +1% unit Δ FMD) and non-responders (< +1% unit Δ FMD) and performed secondary statistical analyses using data produced from the clinical trial. Lastly, to investigate mechanisms for improvements in endothelial function, we used a reverse translational human-to-cell approach leveraging human blood serum collected from participants in the clinical trial to perform ex vivo cell culture experiments. Results from the clinical trial showed that daily blueberry consumption significantly improved FMD/SRAUC compared to baseline by 96%. FMD not normalized for shear rate increased by 1.34% though the effects were not statistically significant (but were clinically significant). Improvements in FMD/SRAUC after blueberry consumption were due to reductions in oxidative stress as responses to ascorbic acid infusion were significantly reduced at 12 weeks in the blueberry group compared to baseline, with no changes in the placebo group. There were no major effects on blood pressure, arterial stiffness, endothelial cell protein expression, or other blood biomarkers of cardiovascular health. It was determined that the blueberry intervention was ~50% effective for improving FMD to clinically relevant levels of ≥ +1%, and that responders had decreased cardiovascular health and higher levels of circulating estrogen at baseline compared to non-responders. After 12 weeks of blueberry consumption, responders had reductions in oxidative stress, lower plasma nitrate levels, and higher phosphorylated endothelial nitric oxide synthase protein expression compared to non-responders. Lastly, we cultured HAECs with 15% serum (blueberry and placebo) for 1 h followed by 200 µM hydrogen peroxide (H2O2) for 24 h to induce endothelial dysfunction and evaluated the effects of blueberry (poly)phenol-rich serum on endothelial cell dysfunction and atherosclerosis progression. There were no statistically significant differences on monocyte binding, insulin-stimulated nitric oxide production, or peroxynitrite concentrations between dysfunctional HAECs treated with blueberry and placebo serum from the clinical trial. Collectively, results from these studies indicate that daily blueberry consumption for 12 weeks improves endothelial function in postmenopausal women with above-normal blood pressure through reductions in oxidative stress, and that efficacy (i.e. degree to which postmenopausal women responded to treatment in endothelial function) seems to be dependent on participant characteristics including cardiovascular risk factors and estradiol at baseline. Due to the inconclusive results regarding the ex vivo experiment, cellular mechanisms by which blueberry (poly)phenol metabolites impact endothelial function and atherosclerosis progression cannot be determined.